POROSITY EVOLUTION IN SNO2 XEROGELS DURING SINTERING UNDER ISOTHERMAL CONDITIONS - Santilli, Celso Valentim [UNESP] (1995)
CONSELHO NACL DESENVOLVIMENTO CIENT & TECNOL,LNLS,BR-13081970 CAMPINAS,SP,BRAZIL